SMEs E-commerce Buying Intention: How the Effect of Perceived Value, Service Quality, Online Customer Review , Digital Marketing and Influencer Marketing - Dewiana Novitasari (Journal of Information Systems and Management (JISMA), 2022)
The purpose of this study was to analyze Relationship between digital marketing and buying intention, influencer marketing on buying intention, online customer reviews service quality on buying intention. perceived value on buying intention.service quality on buying intention.The data is obtained through questionnaires distributed online through social media, the respondents of this study were 550 employees of the SMEs in Banten who were selected through simple random sampling method. Analysis of data processing using Structural Equation Modeling (SEM) with SmartPLS 4.0 software tools. The stages of PLS ​​analysis using smartpls 3 include 3 stages, namely: The outer model testing phase to test the validity & reliability of indicators and constructs, the Goodness of fit model testing phase to test the model's predictive power and model feasibility, The inner model testing phase to test the significance the effect of exogenous variables on endogenous variables. From the research results obtained, it can be concluded Based on the analysis, it can be concluded that Digital Marketing has a positive effect on buying intention, influencer marketing has a positive effect on buying intention, and online customer reviews have a positive effect on buying intention. Digital marketing has an effect on buying intention, considering that the reach to be achieved is very broad. Influencer marketing has an effect on buying intention, while unattractive influencers will cause the decision to buy will also decrease. Online customer reviews have an effect on buying intention.